DO PANDEMIC AND LIFESTYLE CHANGES INFLUENCE THE SHIFT FROM FAST FOOD TO HOME COOKED FOOD? - Adinoto Nursiana; Fongnawati Budhijono; Sutrisno Sutrisno; Meiana Maulida Hikmawati (Pringgitan, 2025)
This study aims to analyze the impact of the COVID-19 pandemic and lifestyle changes on the shift in consumer preferences from fast food to home-cooked meals and to formulate adaptive marketing strategies for culinary businesses. This study is quantitative with a descriptive-inferential verification design. The sample consisted of 150 respondents selected through purposive sampling from the urban consumer population in Indonesia. The research instrument was a Likert-scale questionnaire transformed using the Certainty Method. Data analysis was performed using multiple linear regression analysis with the help of SPSS software. Empirical data testing was conducted at a significance level of 0.05. The results of the study, after undergoing the classical assumption test, indicate that the pandemic and lifestyle changes have a positive and significant effect on the shift in consumption to home-cooked meals. The practical implications of this study suggest that fast food businesses adopt adaptive marketing strategies in the form of product development that emphasizes health and food safety aspects.